Synthesis and Evaluation of Boron-Containing Heterocyclic Compounds with Antimicrobial and Anticancer Activities - Prates, João Lucas Bruno [UNESP]; de Matos Silva, Samanta [UNESP]; Medina-Alarcón, Kaila Petrolina [UNESP]; dos Santos, Kelvin Sousa [UNESP]; Belizario, Jenyffie Araujo [UNESP]; Lopes, Juliana Romano [UNESP]; Marin-Dett, Freddy Humberto [UNESP]; Campos, Debora Leite [UNESP]; Mendes Giannini, Maria José Soares [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Barbugli, Paula Aboud [UNESP]; Pavan, Fernando Rogério [UNESP]; et al. (MDPI, 2025)
Organoboron compounds, especially those containing boronic acid and benzoxaborole in their structure, have been gaining prominence in medicinal chemistry, following the FDA approval of tavaborole for the treatment of onychomycosis and bortezomib for multiple myeloma. The antimicrobial and anticancer effects of organoboron compounds motivate the investigation of the effects of the novel derivatives described here. A total of fourteen new boronic derivatives were synthesized and characterized using analytical methods. The antimicrobial activities were evaluated against M. tuberculosis (Mtb) H37Rv strains and fungal dermatophytes (C. albicans, ATCC 90028; T. rubrum, ATCC 28189; and T. mentagrophytes, ATCC 11481), while the anticancer effect was evaluated against oral squamous cell carcinoma (SCC) cell lines. Several promising boron-containing prototypes were identified, providing a foundation for further molecular optimization in the development of new antimicrobial and anticancer compounds.
Keywords: antimicrobial; benzoxaborole; boron-containing compounds; boronic acid; cancer; fungi; Mycobacterium tuberculosis; organoboron